Acceptance and Implications of Holography Technology for Presenting Minangkabau Traditional Clothing in Museums: A Technology Acceptance Model (TAM) - Afyenni, Rita; Erianda, Aldo; Firosha, Ardian; Hidayat, Rahmat; Gusman, Taufik (SOTVI, 2025)
This study investigates the use of holography technology to present Minangkabau traditional clothing in museums, applying the Technology Acceptance Model (TAM) to assess public response. Survey results show high acceptance, with strong ratings for cultural authenticity and educational value. Perceived ease of use and usefulness significantly influence positive attitudes and behavioral intention, with higher acceptance among females, younger age groups, and those with higher education. Despite these positive outcomes, technical challenges remain, including high implementation costs, limitations in visual clarity, and concerns about digital authenticity. The findings imply that holography can effectively bridge traditional heritage with modern, interactive experiences, making museums more engaging and accessible. The study recommends further research to address technical improvements, cost efficiency, and broader implementation, supporting holography as a strategic tool for cultural preservation and educational innovation.